Business Resilience: Operational Management Strategies for Facing the Global Economic Crisis - Imam Wibowo (SEAN Institute, 2023)
The global economic crisis poses a serious challenge to business continuity throughout the world. This research aims to identify and analyze operational management strategies that are effective in increasing business resilience when facing the global economic crisis. The research methods used involve literature studies, interviews with business practitioners, and case analysis of companies that have successfully survived the previous economic crisis. The research results show that implementing an integrated operational management strategy, involving supply diversification, production flexibility, risk management, operational innovation, and stakeholder involvement, can build strong business resilience in the face of the global economic crisis. Supply diversification and production flexibility provide protection against supply disruptions and rapid adaptation to market changes, while careful risk management helps identify, evaluate and mitigate potential risks. Operational innovation increases competitiveness through the application of new technology and process efficiency, while stakeholder engagement forms a resilient network that supports each other.